Human Fithrah in The Quran Perspective (Study Of Surah Al-'Araf Verse 172 And Ar-Rum Verse 30) And Its Implications in Learning - Abd Halim Nasution (CV. AFDIFAL MAJU BERKAH, 2022)
The actual problem of religious education in schools/madrasas at this time is the incompatibility of the results of religious education taught in schools/madrasas with the demands of religious teachings themselves, religious education tends to be oriented to the process of transferring religious knowledge and has not fully aimed at actualizing human nature as referred to in QS. al-'Araf/ 6:172 and Ar-Rum verse 30, namely individuals who submit and obey hanif. It is necessary to study specifically what the implications of human nature are with learning. Man created by God has physical and psychological potential, the potential that allows him to submit and obey God and become a caliph on earth. For this potential to exist in human life, efforts to grow and develop this religious nature must go through education, guidance, learning, and training both physically and mentally. formal or informal. For this reason, it is necessary to formulate educational/learning objectives, plan learning materials, and implement the learning process that must be in line with human nature.